Impaired temporal resolution of visual attention and DBH genotype in attention deficit hyperactivity disorder (ADHD) - ROBERTSON, IAN (My University, 2006)
Background Dopamine beta hydroxylase (D?H) catalyzes the conversion of dopamine to noradrenaline. Attention-deficit/hyperactivity disorder (ADHD) has been associated with the A2 allele of a Taq I polymorphism of the DBH gene. Since catecholamines regulate visual attention, we examined whether participants with ADHD were impaired on a task requiring temporal attention and how DBH genotype influenced temporal attention in ADHD. Methods Thirty-seven children and adolescents with ADHD and 52 matched, normal control subjects participated. Participants were presented with two visual stimuli, separated in time by either 50, 100, or 200 milliseconds, and were asked to judge the temporal order of their onset. Genotypes for the Taq 1 polymorphism were available for 33 of the ADHD participants. Results Attention-deficit/hyperactivity disorder participants were more error prone than control subjects, particularly when stimuli were presented close together in time (i.e., at the 50 milliseconds asynchrony). Moreover, ADHD individuals homozygous for the A2 allele performed more poorly than those without this allele, and this difference was accentuated at the 50 milliseconds asynchrony. Conclusions Attention-deficit/hyperactivity disorder participants have an impaired rate of perceptual processing for rapidly presented visual events. Deficits in the temporal resolution of visual attention in ADHD are associated with the A2 allele of the Taq I DBH polymorphism or another variant with which it is in linkage disequilibrium.
PUBLISHED
Keywords: Psychology